La influencia del liderazgo en el desarrollo de las competencias laborales (2021)
This research project aims to give the reader important tools on the different concepts of leadership, to demonstrate from a holistic perspective the important or fundamental role that a leader plays in the exercise of his profession or trade, since his role as a leader It has a high impact on the development of the labor competencies of its collaborators. All this with a relevant purpose and that is to bring success to the organization where he leads, with an ethical vision, promoting social responsibility and in turn creating a happy, profitable and sustainable company over time, with its defined and inspiring organizational culture based on values and promises of value that make this an employer branding preferred by its collaborators.